KORELASI PENGGUNAAN GADGET TERHADAP KEPUASAN KOMUNIKASI INTERPERSONAL PADA MAHASISWA DISABILITAS - Nisa Azizah; Arina Rahmatika (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2018)
Gadget in the form of smartphone and laptop is a development of information technology and communication in Indonesia. This development is the reason difabel to use gadget in their daily activities. But each of difabel have different motiv and gratifications in using them. So, the aim of research is there is correlation between the difabel use of gadget and satisfaction of interpersonal communication in UIN Sunan Kalijaga. This is quantitative research with the method of purposive sampling and the collection data by questionnaire. Population of data is 72 person and with sample 32 people. The results obtained from this research is proved hypothesis stating that there is a significant positive correlation between the use of gadgets with the satisfaction of interpersonal communication in difabel UIN Sunan Kalijaga.